Planning for Cikapundung Terrace Development in the Cikapundung River Watershed, Bandung City - Nyimas Riah Afrilianti; Rahmi Aprilianti Dewi (Social Impact Journal, 2023)
Bandung, as one of the centers of development in Indonesia, continues to transform to meet the increasingly complex needs of the community. One development project that has attracted attention is the "Cikapundung Terrace Development Planning in Coblong District." The Cikapundung Terrace symbolizes the harmonious interaction between nature and urbanization, creating a comfortable and sustainable space for the citizens of Bandung. This research adopts a literature study approach, especially in the form of a literature review, with the selection of a narrative review model. The study procedure in this narrative review model involves comparing data from a number of international journals that have been analyzed and then compiled in a summary based on the author''s experience, theories, and relevant models. The research method implemented is qualitative, using data sources in the form of secondary data obtained from a number of international journals, articles, and previous studies that have been analyzed by the author related to the issues that are the focus of this research. This research adopts an analytical descriptive method by collecting, identifying, compiling, and analyzing various data found. From the above explanation, it can be understood that the development of the Cikapundung Terrace provides an opportunity to improve the economy of the community while adding a tourist destination and a place for social activities in the community. At the local level, the presence of Teras Cikapundung creates economic potential in various ways. First of all, the presence of this tourist spot can create direct employment opportunities, such as janitors, recreational facility operators, and administrative personnel. In addition, the emergence of small businesses such as food and souvenir vendors around the Cikapundung Terrace area can have a positive economic impact on local businesses. The Cikapundung basin is a mirror of how urban development can be integrated with sustainability and community well-being. As a successful model, the project can serve as an inspiration for the development of other green open spaces in different regions. Through a joint effort between the government, academic institutions and the community. It can be concluded that the Cikapundung Terrace Development Planning in the Cikapundung River Watershed of Bandung City has achieved its objectives.